2021
DOI: 10.1016/j.dsx.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a questionnaire to assess socio-behavioural impact of COVID-19 on the general population

Abstract: Background and aim The aim of the study is to develop a valid and reliable tool to assess socio-behavioural changes. Methods This mixed method study has two phases. Phase I for questionnaire development (literature review, focus group discussion, expert evaluation and pilot testing). Phase II for establishing construct validity via factor analysis and internal consistency via Cronbach's ɑ by administering the questionnaire on 179 participants. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…This study provides a novel validated tool that can be used to explore aspects of hospital pandemic preparedness, such as knowledge, skills, and mental wellbeing from the perspectives of HCWs themselves. The undertaken validation of the SQIDORP in this study demonstrated satisfactory reliability and validity estimates, and suggested factors that are consistent with available literature [ 47 , 48 ]. The purpose of developing and validating the SQIDORP was to produce a tool that would enable organizations to objectively assess their pandemic plans from the perspectives of the HCWs, thereby eliminating assumptions.…”
Section: Discussionsupporting
confidence: 84%
“…This study provides a novel validated tool that can be used to explore aspects of hospital pandemic preparedness, such as knowledge, skills, and mental wellbeing from the perspectives of HCWs themselves. The undertaken validation of the SQIDORP in this study demonstrated satisfactory reliability and validity estimates, and suggested factors that are consistent with available literature [ 47 , 48 ]. The purpose of developing and validating the SQIDORP was to produce a tool that would enable organizations to objectively assess their pandemic plans from the perspectives of the HCWs, thereby eliminating assumptions.…”
Section: Discussionsupporting
confidence: 84%
“…The scores on the BRS showed that 74.3% of our population had medium to high resilience capacity, where 70.15% possess medium resilience capacity. Behavioural and psychological interventions such as lifestyle modification to improve sleep quality, as well as physical exercise, can significantly aid individuals in returning to their normal or pre-COVID-19 routine and mental states [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This is a mixed-method study conducted in two phases: (i) development of the questionnaire and (ii) validation of developed questionnaire using standardized methodology. [ 9 10 ] The first phase focuses on developing the questionnaire by generating items from literature review and focus group discussions with experts and the target population. In the second phase, the validity and reliability of the developed questionnaire were established using four steps in a sequential manner: expert evaluation to determine content validity, cognitive interviewing to establish face validity, factor analysis to evaluate construct validity, and internal consistency to evaluate reliability.…”
Section: Methodsmentioning
confidence: 99%